Cognitive Structure of Writing Disorders in Russian: What Would Luria Say? - Elena Kozintseva; Anatoly Skvortsov; Anastasia Ulicheva; Anna Vlasova (Zaykova) (Behavioural Neurology)
Acquired disorders of writing in the Russian language have been reported for more than a century. The study of these disorders reflects the history of Russian neuropsychology and is dominated by the syndrome approach most notably by the writings of Luria. Indeed, our understanding of acquired dysgraphia in Russian speakers is conceptualized according to the classical approach in Modern Russia. In this review, we describe the classical approach and compare it to the cognitive neuropsychological models of writing disorders that are developed to explain dysgraphia in English and in other Western European languages. We argue that the basic theoretical assumptions of the two approaches – cognitive and classical or syndrome approach – share similarities. It is therefore proposed that identification of acquired cases of dysgraphia in Russian could potentially benefit from taking the cognitive neuropsychological perspective. We also conclude that adopting elements of the syndrome approach would substantially enrich the understanding of acquired dysgraphia since these offer an insight into processes not described in the cognitive neuropsychological approach.